Use of physical modelling to study how to increase the production capacity by implementing a novel oblong AOD converter. (21st April 2018) - Samuelsson, P.; Ternstedt, P.; Tilliander, A.; Appell, A.; Jönsson, P. G.
Abstract : There is no known example of an AOD converter with oblong cross sections in the literature. Changing the geometry of the converter vessel, from the traditional circular cross sections, to increase converter volume could potentially influence the performance of the converter and in particular the decarburisation rate. To study the feasibility of implementing an oblong converter, physical modelling was used to study the fluid flow of the proposed converter configuration, geometry and number of tuyeres, and the potential influence on the decarburisation rate. Two water models were employed using water containing NaOH and gas injected through six or eight tuyeres as fluids. In the model, CO2 gas was injected and the reaction of CO2 and NaOH was indirectly measured by detecting the pH value of the water. The mixing time is considered to be a good indicator of the decarburisation as kinetics will be diffusion controlled in the latter period of the process. The following three configurations were studied: (i) a circular converter with six tuyeres, (ii) an oblong converter with six tuyeres, and (iii) an oblong converter with eight tuyeres. The mixing time can be used to evaluate the different converter configurations. The average CO2 concentrations based on several experiments, differed by less than 5% between the circular and oblong models after 165 s of injection of air and CO2 . The results also showed that no difference in mixing time could be found when using 6 and 8 tuyeres, respectively in the oblong model, where the CO2 concentrations differed by less than 2% after 165 s of injection time of air and CO2 . Based on the findings, it has been observed that the influence of converter geometry on mixing time is small, it was concluded that decarburisation rate is likely to be the same irrespectively of converter geometry.